China and the Change of Geopolitics in Southeast Asia - Suvakunta, Pittaya (Journal of International Studies, Prince of Songkla University, 2018)
The Changes of China in the 21st century is emerging as political and economic powers of the world. China's new era of Mao Zedong, China has put together a unified land. And China has developed around the turn of the countries in 1978 and more than four decades ago. China has progressed through the military, economic, science and technology. Rise compared with the Western powers. Meanwhile, China is also expanding into the Southeast Asia region. And countries in Southeast Asia began to settle down in a big way of integration into the ASEAN Economic Community (AEC), which can affect the geopolitics of the region in maintaining the balance of power between the Western World (United States) and Eastern World (China), China has expanded the role and influence in the region with a complex interdependence of the transition to the pursuit of geopolitical interests in the region of Southeast Asia.